The Drosophila Sec7 domain guanine nucleotide exchange factor protein Gartenzwerg localizes at the cis-Golgi and is essential for epithelial tube expansion. - Armbruster, K.; Luschnig, S. (Journal of Cell Science, 2012)
Protein trafficking through the secretory pathway plays a key role in epithelial organ development and function. The expansion of tracheal tubes in Drosophila depends on trafficking of coatomer protein complex I (COPI)-coated vesicles between the Golgi complex and the endoplasmic reticulum (ER). However, it is not clear how this pathway is regulated. Here we describe an essential function of the Sec7 domain guanine nucleotide exchange factor (GEF) gartenzwerg (garz) in epithelial tube morphogenesis and protein secretion. garz is essential for the recruitment of COPI components and for normal Golgi organization. A GFP-Garz fusion protein is distributed in the cytoplasm and accumulates at the cis-Golgi. Localization to the Golgi requires the C-terminal part of Garz. Conversely, blocking the GDP-GTP nucleotide exchange reaction leads to constitutive Golgi localization, suggesting that Garz cycles in a GEF-activity-dependent manner between cytoplasmic and Golgi-membrane-localized pools. The related human ARF-GEF protein GBF1 can substitute for garz function in Drosophila tracheal cells, indicating that the relevant functions of these proteins are conserved. We show that garz interacts genetically with the ARF1 homolog ARF79F and with the ARF1-GAP homolog Gap69C, thus placing garz in a regulatory circuit that controls COPI trafficking in Drosophila. Interestingly, overexpression of garz causes accumulation of secreted proteins in the ER, suggesting that excessive garz activity leads to increased retrograde trafficking. Thus, garz might regulate epithelial tube morphogenesis and secretion by controlling the rate of trafficking of COPI vesicles.